Application of slice regularity to functions of a dual-quaternionic variable - Kim, Ji Eun (Carpathian Mathematical Publications, 2021)
In this paper, we present the algebraic properties of dual quaternions and define a slice regularity of a dual quaternionic function. Since the product of dual quaternions is non-commutative, slice regularity is derived in two ways. Thereafter, we propose the Cauchy-Riemann equations and a power series corresponding to dual quaternions.